2008
DOI: 10.1521/suli.2008.38.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐Cultural Features and Sex Profile of the Individuals with Serious Suicide Attempts in Southeastern Turkey: A One‐Year Survey

Abstract: Our objective was to elucidate potential causes of higher rates of suicide attempts in females compared to males in southeastern Turkey through a 1-year survey. Gender-related differences observed in 96 subjects who attempted suicide by poisoning for the first time were as follows: in comparison to male, females were predominantly within the age interval of 15-24 years, experienced more stressful events in the previous week before suicide attempt, had lower education level, and had a lower rate of employment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…This can explain why unemployment had an adverse impact on suicide. Previous studies also discovered that higher unemployment rate can enhance the risk of suicide behaviour and suicide [48][49][50]. In this study, unemployment had more significant impact on female suicide than male suicide.…”
Section: Discussionsupporting
confidence: 50%
“…This can explain why unemployment had an adverse impact on suicide. Previous studies also discovered that higher unemployment rate can enhance the risk of suicide behaviour and suicide [48][49][50]. In this study, unemployment had more significant impact on female suicide than male suicide.…”
Section: Discussionsupporting
confidence: 50%
“…In our sample, financial difficulty was the only 'stated suicide reason' in which men were more prevalent. In southeastern Turkey, Yasan et al also found that the rate of economic problems was significantly higher in males than in females 8 . It is known that economic stressors and poverty increase the propensity towards suicide through association with suicidogenic conditions, including unemployment, financial stress, family instability, and mental troubles 40,41 .…”
Section: Discussionmentioning
confidence: 96%
“…To date, only a small number of research studies have been done about people attempting suicide in Turkey. Yasan et al have studied demographic characteristics of serious suicide attempts in southeastern Turkey 8 . Their aim was to elucidate causes of higher rates of suicide attempts in females compared to males.…”
Section: Introductionmentioning
confidence: 99%
“…The percentages of the teenage cases for both years were similar. Due to this high rate of teenage of suicide rate, suicide prevention for teenage group has to be more comprehensive, multidisciplinary and involve different aspects of life as well as different sectors of society, and national strategies and policies should be developed (17,18). Also emergency physicians who are increasingly given the responsibility of triaging adolescents with mental health problems to crisis intervention and appropriate follow-up treatments.…”
Section: Discussionmentioning
confidence: 99%